Saturday

April 18, 2015

April 18, 2015

Posted by **jennifer** on Monday, January 7, 2008 at 9:39pm.

a 5x -6

b 15x-6

c 15x+6

d -15-6

e -15x+6

- math -
**Reiny**, Monday, January 7, 2008 at 9:44pmif y = 5x -2 then

5x=y+2 and

x = (y+2)/5, then

3x = 3(y+2)/5 and

-3x = -3(y+2)/5 which unfortunately is not one of your answers.

Did you make a typo?

did you mean find -3y ???

then it is even easier, just follow my steps.

**Answer this Question**

**Related Questions**

Algebra - I need help trying to put the correct vocabulary words when solving ...

Algebra - I need help trying to put the correct vocabulary words when solving ...

math - Solve by elimination 5x+y=2 3x+y=1 This is what I got : 3(5x+y=2) -5(3x+y...

algebra - -15(3+x)=-6x-9 -45-15x=-6x-9 -45-15x+15x=-6x+-15x-9 -45=21x-9 -45=x-9...

Math - f(x)=13x^2 -15x-14 g(x)=15x^3+14x^2-15x+12 find f(3) × f(10) + f(-7) × g(...

Math - f(x)=13x^2 -15x-14 g(x)=15x^3+14x^2-15x+12 find f(3) × f(10) + f(-7) × g(...

Math - A stunt pilot is testing a new plane. The equation that models his height...

Math (logarithmic functions) - Those are the only ones I can't seem to resolve. ...

Math - When fully simplified, ignoring non-permissible values,24x^18/6x^3 x x^8/...

lomas - Right answer? 15(x^2+3x) + 7(x^2+3x) - 5(x^2+3x) 15x^2+45x+7x^2+21x + 5...